Association of ileocolic pedicle division with postoperative complications after restorative proctocolectomy and ileal pouch-anal anastomosis for ulcerative colitis - Tzatzarakis, Emmanouil; Herrle, Florian; Reindl, Wolfgang; Altmayer, Nora Corinna; Minas, Dominik; Kienle, Peter; Reißfelder, Christoph; Şandra-Petrescu, Flavius Ionuţ (BMC surgery, 2021)
When performing a restorative proctocolectomy (RPC) with an ileal pouch-anal anastomosis (IPAA), it is common practice to divide the ileocolic artery (ICA) if the patient has a tumor or dysplasia, or in order to gain sufficient length to secure a tension-free anastomosis. However, it is unclear whether there is an association between division of the ICA and the rate of postoperative complications.
Gesehen am 25.05.2023